Rancang Bangun Sistem Informasi Perencanaan Persediaan Bahan Baku Pada PT. Multimega Dutamandiri - Wahyudi, Muchammmad Arief; Sunarto, M.J Dewiyani; Setyawan, Henry Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Controlling raw material stock is not an easy task. Because of that, a company have to plan raw material requirement to fulfill costumer needs so that the quantity and time of fulfillment is suitable. If a company buys too much raw materials whish is make the stock piled up, and increase the holding cost and the risk of damaged goods. However, if the raw materials stock is very low, there is a possibility insufficient stock (stock out) because the raw materials can not be delivered directly and if the raw materials stock is unavailable the production process is stop, the income will be delayed, and costumer trust.The solution to overcome that problem is to make design raw materials requirement planning informastion system. This system is built to counting estimate raw materials request, to counting raw materials demand, and the right time to buy the raw materials.This application will provide an information such us raw materials request report, raw materials forecasting report, and raw materials stock planning report. Based on trial results that has been done, this system could help forecast raw materials demand in the future, raw materials procurement, and the right time to buy the raw materials.Â Â Â